Symbolic Violence and Public Displays of Difference - Compan, Magali (Visualizing Violence in Francophone Cultures, 2015)
Visualizing Violence in Francophone Cultures brings together two complex and powerful loci of meaning: violence and the visual. As such, it offers a comprehensive overview from which one can gain a better understanding of the complexity of the visual rhetoric of violence. The visual representations of violence explored in this volume include both fictional works, including, for example, narrative films, graphic novels, and theatre, and non-fictional genres, such as news media and cultural artifacts. This volume’s strength is also grounded in its interdisciplinary approach; by bringing together scholars from a variety of academic fields to examine a broad range of visual artifacts, such as photography, graphic novel, films, paintings, objects, the book offers a substantive corpus focusing on the rhetoric of violence. The essays collected in this volume explore the ways in which visual expressions of violence have infiltrated diverse narrative forms, and, as such, how they both construct and challenge general understandings of contemporary violence. They all chart, with cultural and historical specificity, the way in which images of violence shape the visual imaginary of ethical worlds.
Keywords: History / General; dept.wll

Sabbatical Leave Report. - Latorre, Sobeira (2015)
The objective of my sabbatical leave was to make progress on a book project tentatively entitled: "In conversation: Dominican women writers speak." This project is a book of interviews with contemporary women writers from the Dominican Republic as well as writers who identify themselves as Domincan-American...
Keywords: dept.wll; faculty_collection; sabbatical_report

Shifting paradigms: A model for the integrated assessment of language and culture - Hammer, J.; Schmitt, E. (Culture and Foreign Language Education: Insights from Research and Implications for the Practice, 2015)
Keywords: dept.wll